Molecular prevalence and genotype identification of Enterocytozoon bieneusi in cattle and goats from Zhejiang Province, China - Xin, Xianming; Sun, Lijie; Liu, Wei; Zhang, Jiayin; Ma, Shiyang; Fu, Xinyi; Zhao, Wei; Yan, Baolong (Frontiers in Veterinary Science, 2024)
IntroductionEnterocytozoon bieneusi (E. bieneusi) is a widespread intracellular fungi that poses a significant zoonotic threat due to its infectivity toward both humans and animals.MethodsTo evaluate the zoonotic transmission potential of this fungi, a molecular investigation was undertaken on E. bieneusi in cattle and goats reared across multiple cities in Zhejiang Province, China. A total of 651 fresh samples were collected, consisting of 265 cattle and 386 goats. The presence of E. bieneusi was determined by PCR amplification and sequencing analysis of the internal transcribed spacer (ITS) region of the small subunit ribosomal RNA (SSU rRNA) gene in all collected samples.ResultsThe results revealed that 17.1% (111/859) of the animals were afflicted with E. bieneusi, cattle having a prevalence of 14.0% (37/265) and goats displaying a higher rate of 19.2% (74/386). Seventeen E. bieneusi genotypes were identified, including 10 known, CHG5 (n = 30), CHG3 (n = 21), I (n = 14), J (n = 12), CHG2 (n = 11), COS-II (n = 8), D (n = 4), CHG19 (n = 2), ETMK5 (n = 1), and Henan III (n = 1), and seven novel, ZJG-I to ZJG-VI and ZJN-I (one each) genotypes.DiscussionThese findings indicate widespread infection of E. bieneusi among the surveyed animals, thereby raising concerns about zoonotic genotypes that could pose potential threats to public health. Furthermore, the identification of novel genotypes of E. bieneusi offers valuable insights into the genetic diversity of this pathogen.